A Development of STEM-Based E-Modules Integrated with Project-Based Learning (PjBL) to Improve Mathematical Reasoning and Creativity in Students at SMP Negeri 1 Telaga, Gorontalo Regency: STEM, project-based learning, mathematical reasoning, creativity, Test instruments, e-modules, - Nosva Adam Yunus; Febiyanti R. Hasan; Suhardiman Darson Tamu; Zulfami Mustapa R (Journal of Innovative and Creativity, 2025)
This study aims to develop and test the validity of pretest and posttest instruments for measuring students' mathematical reasoning and creativity in the development of STEM-based e-modules integrated with the Project-Based Learning (PjBL) model. Mathematical reasoning and creativity are considered higher-order thinking skills that are important in understanding mathematical concepts and solving contextual problems. The research was conducted at SMP Negeri 1 Telaga, Gorontalo Regency, using the ADDIE Research and Development (R&D) model, which was limited to the analysis, design, and instrument development stages. The research instruments were pretest and posttest tests of students' mathematical reasoning and creativity, which were compiled based on competency indicators and mathematical thinking ability indicators. The instruments were validated by subject matter experts and education practitioners using a Likert scale. Data analysis techniques used content validity analysis to determine the level of instrument feasibility. The results showed that the developed pretest and posttest instruments were highly valid and feasible for measuring students' mathematical reasoning and creativity. These findings form the basis for conducting practicality and effectiveness tests of the STEM-PjBL-based mathematics e-module in the next stage of research.